ChemInform Abstract: A Highly Efficient and Recyclable Ligand‐Free Protocol for the Suzuki Coupling Reaction of Potassium Aryltrifluoroborates in Water. Issue 37 (16th September 2014) - Liu, Leifang; Dong, Yan; Tang, Nana
Abstract The applied catalytic system can be recycled at least 8 times without significant loss of activity.